1999
DOI: 10.1159/000008639
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Lavage Promotes Intraperitoneal Adhesion in the Rat

Abstract: This study was designed to study the effect of peritoneal lavage solutions on postsurgical adhesion formation in rats undergoing laparotomy and standardized ischemic injury to the lateral peritoneum with sutures. This reproducible model enabled semiquantitative scoring of adhesion formation. Adhesions were induced in 33 adult female Wistar rats. The solutions RPMI medium, NaCl (0.9%), Viaspan® and both povidone-iodine (1%) and chlorhexidine (0.02%) in dilution were evaluated. In the control group th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
3
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 12 publications
1
30
3
4
Order By: Relevance
“…When saline lavage or installation is included into the experimental groups, three different results are observed; beneficial, [10][11][12][13][14] ineffective, [9,[15][16][17][18] or even harmful. [19,20] Another challenge in peritoneal adhesion studies is the use of several different models. Two major problems caused by peritoneal adhesions are intestinal obstruction and infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When saline lavage or installation is included into the experimental groups, three different results are observed; beneficial, [10][11][12][13][14] ineffective, [9,[15][16][17][18] or even harmful. [19,20] Another challenge in peritoneal adhesion studies is the use of several different models. Two major problems caused by peritoneal adhesions are intestinal obstruction and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…[20] van Westreenen et al have also suggested stimulation of intraperitoneal adhesions with perioperative lavage. [19] In this rat study, uterine horns were attached to the suture placed lateral to the wall of the abdomen, and 10 ml of lavage (25 °C) for 10 min was applied. The lavage solutions were normal saline, povidone-iodine 1%, chlorhexidine 0.02%, RPMI growth (cell culture) medium, and UW (University of Wisconsin solution).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on this issue proved that use of peritoneal lavage was associated with a greater incidence of adhesions than in cases without lavage, and this was repetitively observed with various fluids (10,11). Peritoneal reactions to injected substances, including different solutions, have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to investigate the efficacy of PL in adhesion prevention in the presence of abdominal drainages. Since there is experimental and clinical evidence that crystalloids result in enhanced adhesion formation, we left the matching groups without additional therapy [32,33].…”
Section: Discussionmentioning
confidence: 99%